Christianity, Islamism and Communism - Fraim, John (New Explorations, 2025)
This speculative essay examines the ideological landscape of the modern world through the lens of three dominant “grand narratives”: Christianity, Islamism, and Communism. Moving beyond superficial political conflict, the author explores the deep metaphysical, teleological, and societal differences between these systems—particularly the foundational chasm between theistic faith (in Christianity and Islam) and atheistic materialism (in Communism). Historical moments of tactical alliance between Islamist and Communist movements are acknowledged but shown to be provisional, rooted in opposition to common enemies rather than shared principles. The essay also identifies structural similarities—such as collectivism, utopian vision, and vanguard leadership—that make these ideologies totalizing forces competing for the soul of civilization. Ultimately, the author suggests that America’s unique historical role has been to synthesize seemingly opposed ideals (freedom and equality), and posits that the nation’s future may lie not in fighting these external “isms,” but in forging a new, higher synthesis from the clash of worldviews—a creative, almost Hegelian resolution that could define the next chapter of global history. This work offers a reflective, forward-looking analysis of the unseen ideological forces shaping our era and invites consideration of synthesis over strife.